EMPOWERING FARMERS IN HUSOAK VILLAGE, HUBIKIAK DISTRICT FOR FOOD SECURITY THROUGH RENTENG WELL IRRIGATION SOURCE TECHNOLOGY DISSEMINATION - Tuhuteru, Sumiyati; Mahanani, Anti Uni; Yohanes Rumbiak, Rein Edward; Kusuma Dewi, Yohana Sutiknyawati; Tabuni, Endius; Doga, Konius; Wenda, Endison; Tabo, Opapur; Wenda, Benius; Lengka, Mariana; Himan, Rusina (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
One of the important technologies to increase agricultural production is irrigation technology which can support plant cultivation systems and act as a water reservoir with a water pump machine support. The principle of several wells is to collect water for irrigation in a cylindrical reservoir that is connected to other reservoirs through a capillary tube. The purpose of this activity is to accelerate the food security system through the dissemination of well-conducted irrigation technology which functions in storing and distributing water, especially in the dry season. The method used in the implementation of this activity is socialization and training as well as assistance in making it well-conducted. The results of collaborative activities to build the nation through community service have a positive impact because they can provide sustainable solutions in improving the food security sector of farmers in Husoak Village, Hubikiak District through the development of knowledge related to irrigation systems and water needs for plants by paying attention to the needs of water and nutrients for plants.